Quaternary thin films: A review - Ho, Soon Min (2015)
Quaternary thin films were reported for use as the photo absorber in solar cells because of direct band gap and high optical absorption coefficient. In the past few years, there were a number of reports on the properties of thin films prepared by different deposition methods. Characterization of thin films was reported by various researchers in order to study of materials properties especially suited to solar cell applications.